DESIGN AND IMPLEMENTATION OF SAFETY INSTRUMENTED SYSTEM FOR MINIATURE OF PASTEURIZATION USING PROGRAMMABLE LOGIC CONTROLLER - (NIM : 13313047) ; NINA NUGRAHENI (NIM : 13313056), MAESY
Safety is a factor that can not be ignored in the process industry. One layer of protection to ensure safety in the industry is safety instrumented system (SIS). The design of SIS in the standard ANSI / ISA No. 84.00.01-2004 includes the analysis phase, implementation phase, operation phase, and the verification phase. Miniature of pasteurization at the Laboratory of Instrumentation Management and Control Systems used as a medium of learning to understand the concept of the level of safety and the design of SIS. Risk analysis using the Hazard and Operability Study and Risk Matrix is required to define Safety Integrity Level (SIL) of miniplant of pasteurization. Design of SIS done by making combinations of system configurations. Fault Tree Analysis is used to determine the Probability of Failure on Demand average (PFDavg) required in determining the SIL of each combination of SIS. The addition of SIS on miniature of pasteurization make the Risk Reduction factor (RRF) of the whole system increases for about 83 times compared by before the addition of SIS. The results of the design is then simulated using PLC Allen Bradley RS Logix 5000.